Conversion of chitin derived N-acetyl-d-glucosamine (NAG) into polyols over transition metal catalysts and hydrogen in water. Issue 2 (31st October 2014) - Bobbink, Felix D.; Zhang, Jiaguang; Pierson, Yann; Chen, Xi; Yan, Ning
Abstract : Chitin and its monomer, NAG, could be the alternative source of (N-containing) polyols. Abstract : N -Acetyl-d -glucosamine (NAG), the monomer of the world's second most abundant biopolymer chitin, has been for the first time converted to its corresponding amide/amino substituted sugar alcohols, smaller C2–4 polyols and N -acetylmonoethanolamine (NMEA), over noble metal catalysts in the presence of hydrogen in water. Four commercialized catalysts were investigated, and Ru/C exhibited the best performance—achieving 8.7% NMEA, 6.1% C4 polyols, and 71.9% C6 polyols (N-containing) under 180 °C, 40 bar H2, 1 h with 1 mol% loading. Kinetic studies were conducted, which revealed four major reaction pathways that lead to various products. In particular, retro-aldol reaction-hydrogenation was confirmed to be the pathway forming NMEA. The effects of additives (NaOH and WO3 ) on the reaction were also tested.